Speech Acts Analysis of Spiderman No Way Home Movie as A Medium of Learning Material - Nurmala Dewi; Dhesyalda Angga West Surya (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
A movie is one of the beneficial teaching media. Its main function is for entertainment, but it is a good resource for language learning as well. The dialog in the movie provides material for learning language skills and language structure which can be learned for any element of language. In this research, the writer investigated the language structure focused on speech acts. The study aims to identify the types of speech acts delivered by the main actor in the Spider-man movie, which was used a learning material, along with their frequency. This research was conducted in descriptive qualitative method. The analysis of speech acts used Searleâ€™s theory which divided speech acts into five classifications, commissive, declarative, directive, expressive, and representative. After analyzing, the writer found all types of speech acts in the conversations. Although, the amount utterances of each type are various. Directive (46%) is frequently used in the dialogue followed by expressive (30%) commissive (12%), declarative (6%), and representative (6%). Therefore, expressions such as command, order, request, thank, apology, etc., which are parts of the directive and expressive type, often appear in conversation, especially in action movies.Â Keywords: Speech act, learning material, movie